Is biological larviciding against malaria a starting point for integrated multi-disease control?: Observations from a cluster randomized trial in rural Burkina Faso - Dambach, Peter; Bärnighausen, Till; Yadouleton, Anges; Dambach, Martin; Traoré, Issouf; Korir, Patricia; Ouedraogo, Saidou; Nikiema, Moustapha; Sauerborn, Rainer; Becker, Norbert; Louis, Valérie R. (PLOS ONE, 2021)
Objectives To evaluate the impact of anti-malaria biological larviciding with Bacillus thuringiensis israelensis on non-primary target mosquito species in a rural African setting. Methods A total of 127 villages were distributed in three study arms, each with different larviciding options in public spaces: i) no treatment, ii) full or iii) guided intervention. Geographically close villages were grouped in clusters to avoid contamination between treated and untreated villages. Adult mosquitoes were captured in light traps inside and outside houses during the rainy seasons of a baseline and an intervention year. After enumeration, a negative binomial regression was used to determine the reductions achieved in the different mosquito species through larviciding. Results Malaria larviciding interventions showed only limited or no impact against Culex mosquitoes; by contrast, reductions of up to 34% were achieved against Aedes when all detected breeding sites were treated. Culex mosquitoes were captured in high abundance in semi-urban settings while more Aedes were found in rural villages. Conclusions Future malaria larviciding programs should consider expanding onto the breeding habitats of other disease vectors, such as Aedes and Culex and evaluate their potential impact. Since the major cost components of such interventions are labor and transport, other disease vectors could be targeted at little additional cost.
Gesehen am 10.09.2021